MANAGING LOCAL INDEPENDENCE: THE ROLE OF TRADITIONAL LEADERS IN BUILDING THE CHARACTER OF ULUN LAMPUNG - Wahyudin, Wahyudin; Wahyudi, Dedi; Khotijah, Khotijah (AKADEMIKA: Jurnal Pemikiran Islam, 2020)
Abstract This paper unpacks the management of local independence owned by the indigenous people of Lampung. The local independence of the indigenous people of Lampung in the form of Piil Pesenggiri philosophy of life needs to be managed as an asset or capital in shaping the character of the community. Piil Pesenggiri which includes four pillars, namely juluk adok, nemui nyimah, nengah nyappur and sakai sambayan contains noble values is important to be passed on and transformed to society. The focus of this study is on the role of traditional leaders (penyimbang) in building the character of ulun (people) Lampung based on the management of local independence. The data used this paper were obtained through observation, interviews and text analysis. Traditional leaders (penyimbang) manage their local independence through several sectors such as education, customary institutions, government institutions, community organizations, and religious institutions. Meanwhile, the role of traditional leaders (penyimbang) includes reconciling disputes, transforming and instilling the noble values ​​of Piil Pesenggiri, encouraging local languages ​​to be local content in education, and taking part in physical and non-physical development to advance the Lampung region. Keywords: traditional leaders, ulun Lampung, piil pesenggiri local independence